ON THE TRACE OF WHO WE ARE, KNOTS? IDENTITIES BETWEEN IDENTIFICATIONS AND DISIDENTIFICATIONS (TEL Tempo, Espaço e Linguagem, 2023)
This essay reflects on identity(ies), equality and diferences, inequalities and similarity, between identifications and disidentifications, in the fields of the Sociology of the postmodern in Stuart Hall and the Philosophy of Modern Times in Jacques Rancière. The content, set by Antonio Gramsci, finds forms, inspired by Language studies, of ambiguity as that which can close the sense, and of the hyphen as that which allows to expand the senses. As a means this author suspends the rehearse in time-space to narrate a history. By starting from the end, the assayer implies that similarity marks the knots in the differences by identifying, and arrives at the principal where equality undoes the knots of inequalities by disidentifying.